Use of rhodamine B to mark the body and seminal fluid of male Aedes aegypti for mark-release-recapture experiments and estimating efficacy of sterile male releases. - Brian J Johnson; Sara N Mitchell; Christopher J Paton; Jessica Stevenson; Kyran M Staunton; Nigel Snoad; Nigel Beebe; Bradley J White; Scott A Ritchie (Public Library of Science (PLoS), 2017)
BACKGROUND:Recent interest in male-based sterile insect technique (SIT) and incompatible insect technique (IIT) to control Aedes aegypti and Aedes albopictus populations has revealed the need for an economical, rapid diagnostic tool for determining dispersion and mating success of sterilized males in the wild. Previous reports from other insects indicated rhodamine B, a thiol-reactive fluorescent dye, administered via sugar-feeding can be used to stain the body tissue and seminal fluid of insects. Here, we report on the adaptation of this technique for male Ae. aegypti to allow for rapid assessment of competitiveness (mating success) during field releases. METHODOLOGY/PRINCIPLE FINDINGS:Marking was achieved by feeding males on 0.1, 0.2, 0.4 or 0.8% rhodamine B (w/v) in 50% honey solutions during free flight. All concentrations produced >95% transfer to females and successful body marking after 4 days of feeding, with 0.4 and 0.8% solutions producing the longest-lasting body marking. Importantly, rhodamine B marking had no effect on male mating competitiveness and proof-of-principle field releases demonstrated successful transfer of marked seminal fluid to females under field conditions and recapture of marked males. CONCLUSIONS/SIGNIFICANCE:These results reveal rhodamine B to be a potentially useful evaluation method for male-based SIT/IIT control strategies as well as a viable body marking technique for male-based mark-release-recapture experiments without the negative side-effects of traditional marking methods. As a standalone method for use in mating competitiveness assays, rhodamine B marking is less expensive than PCR (e.g. paternity analysis) and stable isotope semen labelling methods and less time-consuming than female fertility assays used to assess competitiveness of sterilised males.